Incidence of unplanned oophorectomy at laparoscopic ovarian cystectomy for clinically benign cysts. (November 2014) - Pinto, R. M.; Michos, G.; Papageorgiou, G.; Halmos, G.; Moustafa, M.; Magos, A.
Abstract Laparoscopic surgery is the preferred approach in women with ovarian cysts and a low risk of malignancy, and the aim in young women should be to preserve the ovary. We are not aware of any data on the success of conservative surgery in preserving the affected ovary and this is the reason why we decided to investigate the incidence of unplanned oophorectomy, when a woman is originally scheduled for laparoscopic ovarian cystectomy for clinically benign cysts. We reviewed the medical notes of the 123 women who underwent surgery for clinically benign ovarian cysts between November 2004 and May 2012. The operative procedures performed were ovarian cystectomies (n = 119), salpingo-oophorectomy (n = 2) and fenestration (n = 2). In total, 61 women underwent a concomitant procedure. In our study, we found that planned laparoscopic cystectomy was mostly successful, with only 1.6% of patients in our series requiring unplanned oophorectomy.